Eicosapentaenoic Acid Inhibits KRAS Mutant PancreaticCancer Cell Growth by Suppressing Hepassocin Expression and STAT3 Phosphorylation - Ching-Feng Chiu (Biomolecules, 2021)
Background: The oncogenic Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation was reported to be the signature genetic event in most cases of pancreatic ductal adenocarcinoma (PDAC). Hepassocin (HPS/FGL1) is involved in regulating lipid metabolism and the progression of several cancer types; however, the underlying mechanism of HPS/FGL1 in the KRAS mutant PDAC cells undergoing eicosapentaenoic acid (EPA) treatment remains unclear. Methods: We measured HPS/FGL1 protein expressions in a human pancreatic ductal epithelial (HPNE) normal pancreas cell line, a KRAS-wild-type PDAC cell line (BxPC-3), and KRAS-mutant PDAC cell lines (PANC-1, MIA PaCa-2, and SUIT-2) by Western blot methods. HEK293T cells were transiently transfected with corresponding KRAS-expressing plasmids to examine the level of HPS expression with KRAS activation. We knocked-down HPS/FGL1 using lentiviral vectors in SUIT-2 cells and measured the cell viability by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and clonogenicity assays. Furthermore, a lipidomic analysis was performed to profile changes in lipid metabolism after HPS/FGL1 knockdown. Results: We found that the HPS/FGL1 level was significantly upregulated in KRAS-mutated PDAC cells and was involved in KRAS/phosphorylated (p)-signal transduction and activator of transcription 3 (STAT3) signaling, and the knockdown of HPS/FGL1 in SUIT-2 cells decreased cell proliferation through increasing G2/M cell cycle arrest and cyclin B1 expression. In addition, the knockdown of HPS/FGL1 in SUIT-2 cells significantly increased omega-3 polyunsaturated fatty acids (PUFAs) and EPA production but not docosahexaenoic acid (DHA). Moreover, EPA treatment in SUIT-2 cells reduced the expression of de novo lipogenic protein, acetyl coenzyme A carboxylase (ACC)-1, and decreased p-STAT3 and HPS/FGL1 expressions, resulting in the suppression of cell viability. Conclusions: Results of this study indicate that HPS is highly expressed by KRAS-mutated PDAC cells, and HPS/FGL1 plays a crucial role in altering lipid metabolism and increasing cell growth in pancreatic cancer. EPA supplements could potentially inhibit or reduce ACC-1-involved lipogenesis and HPS/FGL1-mediated cell survival in KRAS-mutated pancreatic cancer cells.